Inhibitory effects of peppermint extracts on the browning of cold-stored fresh-cut taro and the phenolic compounds in extracts - Yuan, Xiao; Tang, Binglin; Wang, Yukun; Jiang, Yuanyuan; He, Jinming; Wang, Guang; Yang, Pandi; Wang, Bin (Frontiers in Sustainable Food Systems, 2023)
Fresh-cut taros are prone to browning even though they are stored at low temperatures, which leads to the quality deterioration and markedly limits the shelf life. The browning control of fresh-cut food with natural substances has received much attention. This study evaluated anti-browning potential of peppermint extracts in fresh-cut taro during cold storage. The results showed that both peppermint leaf and shoot extract (LE and SE) treatments could effectively retard the browning of fresh-cut taros. Furthermore, LE and SE treatments reduced the activities of phenylalanine ammonialyase and lipoxygenase, the contents of total phenolic compound (TPC), total flavonoids, soluble quinones, malondialdehyde and hydrogen peroxide, enhanced peroxidase activity and antioxidant capacity in taro slices. The TPC contents were reduced by 4.05 and 17.71%, and the T-AOC was enhanced by 28.73 and 28.82% as compared to the control at 12 d. These results together suggested that peppermint extract treatments reduced phenolic biosynthesis but enhanced antioxidant activity. However, LE and SE treatments did not inhibit polyphenol oxidase (PPO) activity, suggesting that peppermint extract treatments reduced taro browning was not through inhibition of phenolic oxidation. More than 240 phenolic-related compounds including caffeic acid, ferulic acid and p-Coumaric acid were identified in peppermint extracts through UPLC–MS/MS analysis, suggesting that phenolics may be bioactive substances reducing taro browning. In conclusion, this study demonstrates that peppermint extract is a promising natural anti-browning ingredient and phenolic compounds may function on taro browning inhibition.